Countering Prompt Global Strike: The Russian Military Presence in Syria and the Eastern Mediterranean and Its Strategic Deterrence Role. Issue 1 (2nd January 2019) - Thornton, Rod
ABSTRACT: This article examines the Russian military involvement on land in Syria and in the Eastern Mediterranean Sea. It considers, in particular, why the point is constantly being made in Russian political and military circles that these two commitments will be 'permanent' in nature. It begins by providing the rationales for the initial establishment of a Russian Eastern Mediterranean naval flotilla and the later sending of ground troops with air support to Syria. It goes on to show what benefits — geopolitical, political, military, and, in particular, strategic — have accrued to Russia from the combination of these two missions. The article concludes by showing that these benefits are too substantial for any Russian political leader to contemplate a withdrawal from Syria at any point in the foreseeable future.